Durability performance of CNT and nanosilica admixed cement mortar. (20th January 2018) - Lee, Han Seung; Balasubramanian, B.; Gopalakrishna, G.V.T.; Kwon, Seung-Jun; Karthick, S.P.; Saraswathy, V.
Highlights: The synergistic effect of NS with CNT composite cement mortar was investigated. Strength and durability properties were enhanced by the addition of NS and CNT. Polarization study revealed that the corrosion resistance was enhanced. SEM and XRD confirmed that NS and CNT accelerated the hydration process and resulted in denser microstructure formation. Abstract: In the recent years, development and use of nanomaterials are gaining importance in the construction industries due to the advancement of science and technology. In the present investigation, nanosilica (NS) was synthesized from rice husk ash and characterized using XRD, Particle size analysis and SEM techniques. 1% NS by weight was used in cement mortar along with carbon nano tube (0.01%–0.07%) as a cement replacement materials and rock dust (RD) was used as a replacement for river sand. Five different mix combinations were formulated. Polycarboxylate based water reducing admixture was used for improving the workability of the mix. All the combination of mixes derived were subjected to compression, split tensile test, and durability studies such as sorptivity, water absorption, and chloride penetration test. Potentiodynamic polarization study was carried out to understand the corrosion performance of the composite cement mortar. SEM and XRD studies were carried out for the hydrated products of the composite cement mortar. The results showed that NS and CNT increased the compressive strength by 12%–76% and enhanced the corrosion resistance properties than the control.